Deforestation Trends in the Congo Basin : Reconciling Economic Growth and Forest Protection - Megevand, Carole (Washington, DC: World Bank, 2013)
The Congo Basin forests have been mainly “passively” protected by chronic political instability and conflict, poor infrastructure, and poor governance. Congo Basin countries thus still fit the profile of high forest cover/ low deforestation (HFLD) countries. However, there are signs that Congo Basin forests are under increasing pressure from a variety of sources, including mineral extraction, road development, agribusiness, and biofuels, in addition to subsistence agricultural expansion and charcoal collection.